Spider venom peptides with unique fold selectively block Shaker-type potassium channels - Alexey I. Kuzmenkov; Valentina A. Iunusova; Vladislav A. Lushpa; Yakov A. Deyev; Vladislav V. Babenko; Daniil V. Osipov; Antonina A. Berkut; Jan Tytgat; Eduard V. Bocharov; David J. Adams; Rocio K. Finol-Urdaneta; Alexander A. Vassilevski (Cellular and Molecular Life Sciences)
Abstract Natural toxins are highly effective at targeting ion channels with high selectivity and potency. To date, all identified spider venom peptide toxins that modulate voltage-gated potassium (KV) channels inhibit Shab (KV2) or Shal-related isoforms (KV4) by interacting with their voltage-sensing domains. In this study, we report novel spider-derived pore-blocking toxins that selectively target Shaker-type (KV1) channels with nanomolar potency. We isolated murinotoxins MnTx-1 and MnTx-2 from the orange baboon tarantula Pterinochilus murinus and sequenced them using a combination of Edman degradation, mass spectrometry, and venom gland nanopore transcriptomics. MnTx-1 was produced recombinantly, and its NMR solution structure was determined. Although MnTx-1 shares sequence motifs common to spider toxins, it displays a distinctly different three-dimensional structure, featuring an alternative disulfide linkage, which we have termed the Disulfide-Reined Hairpin (DRH). We attribute the unique pharmacology of MnTx-1 to its unusual spatial structure. The DRH motif represents a promising new miniature scaffold for future bioengineering applications.